Goats Follow Human Pointing Gestures in an Object Choice Task - Nawroth, Christian; Martin, Zoe M.; McElligott, Alan G. (Frontiers in Psychology, 2020)
Dogs (Canis lupus familiaris) are extremely adept in interpreting human-given cues, such as the pointing gesture. However, the underlying mechanisms on how domestic non-companion species use these cues are not well understood. We investigated the use of human-given pointing gestures by goats (Capra hircus) in an object-choice task, where an experimenter surreptitiously hid food in one of two buckets. Subjects first had to pass a pre-test where the experimenter indicated the location of the food to the subject by a proximal pointing gesture. Subjects that succeeded in the use of this gesture were transferred to the actual test. In these subsequent test trials, the experimenter indicated the location of the food to the subject by using three different pointing gestures: proximal pointing from a middle position (distance between target and index finger: 30 cm), crossed pointing from the middle position (distance: 40 cm), asymmetric pointing from the position of the non-baited bucket (distance: 90 cm). Goats succeeded in the pointing gestures that presented an element of proximity (proximal and crossed) compared to when the experimenter was further away from the rewarded location (asymmetric). This indicates that goats can generalise their use of the human pointing gesture but might rely on stimulus/local enhancement rather than referential information. In addition, goats did not improve their responses over time, indicating that no learning took place. The results provide a greater understanding of human-animal interactions and social-cognitive abilities of livestock, which allows for the provision of enhanced management practices and welfare conditions.